2020
DOI: 10.1111/psyg.12616
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducational intervention on burden and emotional well‐being addressed to informal caregivers of people with dementia

Abstract: Background: In dementia it is necessary that a family member become an informal caregiver. This labour has social, physical and emotional repercussions on the caregiver's health. The objective was to assesses the impact of the INFOSA-DEM intervention on burden and emotional well-being among caregivers of people with dementia, evaluating the effects at 3 and 6 months. Method: We adopted an experimental, non-randomised design with an intervention group and a control group. The intervention group received the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
10
2
Order By: Relevance
“…Concerning the effect of the psychological rst aid program on psychological wellbeing among caregivers of patients with Alzheimer's disease, the present study showed that there is a remarkable highly signi cant increase in the psychological wellbeing among caregivers after the application of the PFA program with a mean difference of 4.75 and large effect size 1.32. A study by Frias, Risco, & Zabalegui, 2020 contradicted the present study and found that applying psycho-educational intervention on the burden and emotional well-being among informal caregivers of people with dementia can lead to a slight insigni cant improvement in the psychological wellbeing among them, because of low perceived social support (21) .…”
Section: Resultscontrasting
confidence: 87%
“…Concerning the effect of the psychological rst aid program on psychological wellbeing among caregivers of patients with Alzheimer's disease, the present study showed that there is a remarkable highly signi cant increase in the psychological wellbeing among caregivers after the application of the PFA program with a mean difference of 4.75 and large effect size 1.32. A study by Frias, Risco, & Zabalegui, 2020 contradicted the present study and found that applying psycho-educational intervention on the burden and emotional well-being among informal caregivers of people with dementia can lead to a slight insigni cant improvement in the psychological wellbeing among them, because of low perceived social support (21) .…”
Section: Resultscontrasting
confidence: 87%
“…Concerning the effect of the PFA program on psychological wellbeing among caregivers of patients with AD, the present study showed that there was a significant increase in psychological wellbeing among caregivers after the application of the PFA program, with a mean difference of 4.75 and a large effect size of 1.32. A study by Frias, Risco, & Zabalegui, 2020 contradicted the present study and found that applying psychoeducational intervention on the burden and emotional well-being among informal caregivers of people with dementia can lead to a slight insignificant improvement in psychological wellbeing among them because of low perceived social support [ 60 ].…”
Section: Discussioncontrasting
confidence: 71%
“…Psychoeducation has been shown to reduce depression, enhance mastery and overall quality of life (Cheng and Zhang, 2020). Psychoeducational programs encourage information sharing, emotional, and social support for caregivers, emphasising engagement in pleasure activities to increase emotional wellbeing while providing skill training and support (Frias et al, 2020). However, the literature recognizes common barriers to attendance and participation in these programs, including transportation issues, care costs, insufficient time due to caregiving/or work obligations, personal health issues and the lack of awareness for specific training needs (Abreu et al, 2015).…”
Section: Psychological Interventions To Reduce Caregiver's Burdenmentioning
confidence: 99%